Low-cost, multi-purpose handheld and next generation soil-plant sensors to drive quality through the agricultural value chain - CGIAR Research Program on Water, Land and Ecosystems (2020)
Beta version of handheld Near-Infrared scanner developed by ICRAF and partners. Scheduled for commercial production.